Nomenclatural value of dialectal features from the point of view of marginal Northern Samogitians - Vyniautaitė, Simona (Baltistica, 2025)
This article presents research on the nomenclatural value of dialectal features from the point of view of Northern Samogitians. It attempts to identify the dialectal features that the residents of the marginal areas of the Northern Samogitian subdialects of Telšiai and Kretinga perceive as the distinguishing features of these subdialects, and to determine the nomenclatural value of some of the most frequently mentioned features – affricates and regressive vowel assimilation. The analysis of the dialectal material of the first two decades of the 21st century – the audio recordings of informants – is based on the methods of dynamic dialectology and perceptual dialectology. The results show that the informants identify quite a variety of phonetic features, but from their point of view, the most distinctive dialectal feature distinguishing Northern Samogitians is the correspondence of affricates č (/tʃ/) and dž (/dʒ/). The differential meaning of the main distinguishing feature of the Northern Samogitian subdialects – regressive vowel assimilation – is defined in a more complex way. In some cases, this feature is observed quite easily and is considered very distinctive, but much more often it is hardly perceived by the information providers as the main distinguishing feature of the representatives of the Northern Samogitian subdialects of Kretinga and Telšiai. The informants’ attitudes essentially reflect a greater closeness to Antanas Salys’ dialect classification; at the same time, they could be the result of the regiolectal and geolectal structure.